Distribution of Micronutrient forms Along Duny Landscape - Joshi, D C; Dhir, R P (Annals of Arid Zone, 2016)
Different forms of Fe, Mn, Zn and Cu in duny landscape of two rainfall zones of Indian arid region have been reported. The dune and interdunal soils of higher rainfall zone contained more of HCl soluble Mn, Zn and Cu; free Fe and Mn; reducible and active Mn and DTPA-Mn than their counter parts in the low rainfall zone. In both the rainfall zones, interdunal soils contained higher amounts of these constituents. DTPA-Fe and Zn were more in the dune soils of low rain fall zones and in both the rainfall zones interdunal soils contained less amounts than the associated dunes. Most of these soils appeared well provided with the iron, copper and zinc but deficient in manganese content.